Políticas educacionais e processo de avaliação institucional na Universidade Estadual de Goiás - Campus Goianésia (2005 e 2015) - Rodrigues, Euzeanne Elias de Souza (2017)
The present research is based on qualitative approach, documentary research and comparative studies among Self- evaluation conceptions, processes and methodological procedures at the State University of Goiás (UEG – Universidade Estadual de Goiás), - Goianésia Câmpus, years 2005 and 2015. The research object is the educational policies and the Institucional Evaluation process in UEG. The general objective is to carry out comparative studies for the years 2005 and 2015 of the Self-evaluation process involving students and teachers of the mentioned Câmpus, aiming to contribute to the improvement of the UEG purpose and objectives: a public, state, statal, Multicampi and interiorized university. Thus the problem of the research is stated: What relations can be established between the UEG's Self-evaluation process, in the years 2005 and 2015, based on the analysis of the assessment carried out by students and teachers. The specific objectives are: a) to describe the historical context and the university construction process, Institucional Evaluation and educational policies in UEG, in the decade 2000; B) to investigate how the Brazilian higher education policies subsidized the implementation of the UEG's Institucional Evaluation, in view of the institution of the National Higher Education Assessment System (Sinaes - Sistema Nacional de Avaliação da Educação Superior), created by Law no. 10.861, at April 14 th , 2004; C) to analyze, through comparative studies, the process of institutionalization and development of the self assessment and the assessment culture, conceived as a research at UEG - Goianésia Câmpus. The adopted method was the dialectical historical materialism. The theoretical foundation is based on the conception of institutional evaluation, internal and external assessment, carried out by state and federal government agencies and the assessment culture conception as a continuous process of subsidies offers to the academic community, with socialization and wide dissemination of the Potentialities and weaknesses of all UEG undergraduate courses. This foundation is based on ideas of: Brzezinski (2005, 2010, 2014); Cabral Neto et al (2007, 2014); Cunha (1983, 1988, 1989); Dias Sobrinho (1996, 2000, 2001, 2003); Leite (2005); Paula (2002); Rossato (1998); Verger (1990), Queiroz (2011), Afonso (2001). The analyses between the years under study assert the disparity in the Institucional Evaluation conception present in the self assessment as follows: The responsible for the assessment of 2005 bear an internal assessment developed as a research, in 2015 the assessment is conceived as a management tool. After 10 years the proposed dimensions and goals have not been reached yet. It is understood that there is a need of changes in the current models and functions of the Institucional Evaluation in UEG, however, the dimensions and axes defragmentation, as done in 2005, is not the solution, since it makes it impossible the compliance with the principle of the totality of the evaluative process presented since 2005. It is considered necessary to stimulate the replanning and decision- making to overcome the weaknesses and better qualify the potentialities revealed by the assessment process of the undergraduate courses in Administration, History, Pedagogy and Information Systems in Goianésia Câmpus. Participatory actions of the entire academic community of the Câmpus of Goianésia are recommended so that the process of Self-evaluation results in a continuous, procedural and immersive evaluation culture not carried out in relation to teaching, research and extension yet.